MOTIVASI MEMBACA SISWA SEKOLAH DASAR MELALUI MEDIA PEMBELAJARAN BERBASIS SASTRA ANAK - Tiara Sevi Nurmanita; Rani Darojah; Khaerul Anam (Vokal: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2022)
This study aims to discuss the use of children's literature as a means of increasing student reading motivation at the elementary school level. This research method is qualitative research using descriptive methods to make a systematic and accurate description based on the facts and phenomena investigated. The results showed that motivation in reading is one of the movements of character education in children, which is a way to increase students' interest in reading. One of the media used in increasing motivation to read indirectly is to use children's literary media. Many kinds of children's literature can be melted down as a form of media material that is of interest to students. The variegated form of children's literature, can provoke students to read.